"The aporia of the veil: the influence of Walter Benjamin's aura in contemporary sound studies". Issue 1 (2nd January 2020) - Chinn, Lisa
ABSTRACT: Walter Benjamin's seminal essay "The Work of Art in the Age of Technological Reproducibility" has recently shaped discussions in sound studies. However, the main theoretical apparatus of the Artwork essay, the aura, lacks sustained attention in sound studies scholarship. While sound studies scholars use analogy to refocus the essay towards sonic reproducibility, they have heretofore missed an important opportunity to analyse Benjamin's framework for the aura. Reading the etymology of "aura" is a sonic concept at its very foundation shows how it. However, a sonic aura should not be taken as an ending point of this essay, because the auratic structure itself is problematic for sound studies scholars. Pierre Schaeffer's influential study of the sound object uses a similar framework characterised by the acousmatic. In this framework, Schaeffer claims that the acousmatic veil disconnects sight from sound, producing what he calls the "sound object" ( l'objet sonore ). Schaeffer argues for both a transcendent and immanent logic of the veil. Transcendence and immanence cannot both underpin experience at the same time and are two philosophically incompatible concepts.